Electrogenic metals in epidermis: connection with cell bioenergetics - V. I. Petukhov; E. V. Dmitriev; L. K. Baumane; A. V. Skalny; Y. N. Lobanova (Acta Biomedica Scientifica, 2016)
We have found out in our previous studies that results of quantitative spectrometry of electrogenic metals (Ca, K, Na) in epidermal cells (hair) of healthy people and the Chernobyl liquidators (chronic oxidative/nitrosative stress) are conjugated. The nature of this «conjugation», like many intimate mechanisms of the metal-ligand homeostasis in the epidermis, remains unsolved. Transmembrane traffic of electrogenic metals (and especially the Na+ ion) is directly related to cell bioenergetics. Therefore, intracellular bioenergetics processes in the membrane and in the mitochondrial respiratory chain, can determine homeostasis of electrogenic metals. It has been shown that in the cell, that is an open dynamic system, there are signs of self-organized criticality (SC). Thus we can classify electrogenic metal homeostasis as SC-phenomenon.